Characterization of F75-HAP produced by Powder Metallurgy method - Nur Maizatul Shima, Adzali; Shamsul Baharin, Jamaludin; Mohd Nazree, Derman; Nur Hidayah, Ahmad Zaidi (Universiti Malaysia Perlis, 2010)
Organized by School of Materials Engineering & Sustainable Engineering Research Cluster, 1st - 2nd December 2009 at Putra Brasmana Hotel, Kuala Perlis, Perlis.